Emotional expressions by sports teams: An analysis of World Cup soccer player portraits (2019)
Emotion display serves as incentives or deterrents for others’ in many social interactions. We study the portrayal of anger and happiness, two emotions associated with dominance, and its relationship to team performance in a high stake environment. We analyze 4318 pictures of players from 304 participating teams in twelve editions (1970–2014) of the FIFA Soccer World Cup, and use automated face-reading (FaceReader 6) to evaluate the display of anger and happiness. We observe that the display of both anger and happiness is positively correlated with team performance in the World Cup. Teams whose players display more anger, an emotion associated with competitiveness, concede fewer goals. Teams whose players display more happiness, an emotion associated with confidence, score more goals. We show that this result is driven by less than half the players in a team. © 2018 Elsevier B.V.